The Influence of Self-Esteem on Narcissistic Behavior of High School Students - Irma Yuniar; Imaduddin, Aam; Muhamad Muhajirin (IKIP Siliwangi, 2025)
The purpose of this study is to describe and analyze the effect of self-esteem on narcissistic behavior. The research method used is a survey method with a quantitative approach. The sample of this study consisted of 216 respondents, who were grade XI students at SMAN 6 Tasikmalaya, who were selected through a simple random sampling technique. Data were collected through observation and questionnaire distribution techniques. The data analysis technique used was simple linear regression. The results showed that the F count was 5.674 or sig 0.018 (p<0.05), then self-esteem significantly positively influences narcissistic behavior. The research conclusion reveals that the influence of self-esteem is smaller than the influence of other external factors, which can be a clue that external factors have a greater role in influencing students than their sense of self-worth. This research contributes as a reference for schools, especially guidance and counseling (BK) teachers, in developing programs to strengthen healthy self-esteem in students. This aims to prevent excessive narcissistic behavior and encourage the development of a balanced personality.